The Impact of Unions on Wages in Brazilian Manufacturing - Jorge Saba Arbache (University of Kent, Department of Economics, 1998)
The empirical literature on the impact of unions on wages has stressed two major conclusions. Firstly, unionised workers earn a wage premium when compared to comparable nonunionised workers. Secondly, the dispersion of wages within the union sector is lower than in the nonunion sector. We examine the validity of these findings in the context of a developing country labour market. Our results show that unionism does create a positive wage differential for male, semi-skilled workers with formal labour contracts in Brazilian manufacturing, and that, contrary to the common finding in the existing literature, wage dispersion is greater in the union sector. We show that these findings can be explained by the greater variance in the characteristics of unionised workers, the vulnerability of nonunionised workers to market conditions, and the structure of wage bargaining.
Keywords: J31; J51; 330; Union power; union wage differential; wage dispersion; Brazil; Lohnstruktur; Lohnpolitik; Industrie; Theorie; Brasilien